Bubbles in history - William Quinn; John D. Turner (Queen's University Centre for Economic History (QUCEH), 2020)
Bubbles have become ubiquitous. This ubiquity has stimulated research over the past three decades into bubbles in history. In this article, we provide a systematic overview of research into historical bubbles. Our analysis reveals that there is no coherent approach to the study of bubbles and much of the debate has unhelpfully focussed on the rationality/irrationality dichotomy. We then suggest a new framework for the study of historical bubbles, which helps us understand the causes of bubbles and their economic consequences. We conclude by suggesting ways in which business history can contribute to the study of historical bubbles.
Keywords: G01; G10; G40; N10; N20; N80; 330; Bubbles; Business History; Speculation